Development of a strategic plan for the sport of futsal in Iraq - Hasanain Hadi Bachay Alshiblawi; Mahdi Talebpour; Seyyed Morteza Azimzadeh; Mohammad Kashtidar (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.